Tobacco Price Increases and Population Interest in Smoking Cessation in Japan Between 2004 and 2016: A Google Trends Analysis. Issue 4 (31st January 2018) - Tabuchi, Takahiro; Fukui, Keisuke; Gallus, Silvano
Abstract: Introduction: Tobacco price increases can generate increased public interest in smoking cessation, but it is not clear how long this interest lasts. Our objective was to evaluate the duration of the impact of cigarette price increase in Japan using Google search data. Methods: Monthly or daily aggregated Google search volume for smoking cessation in Japan from 2004 to 2016 was collected in terms of relative search volume (RSV) ranging from 0 to 100. Using monthly RSV data, we evaluated possible relationships between the RSVs and tobacco control measures in Japan. Time periods within which the impact of search volume significantly increased were identified by cluster detection test, using daily RSV data. A spike in RSV preceding the enforcement of a cigarette price increase revealed an anticipation effect. Results: Between 2004 and 2016, the three highest monthly RSV spikes were observed in July 2006 (RSV = 66), when cigarette prices increased by 11%, and in September (RSV = 90) and October 2010 (RSV = 100), when cigarette prices increased by 37%. Regarding daily RSV, the detected cluster size around the price increase in 2010 (52 days) was longer than that in 2006 (17 days). In 2010, a cluster period of 25 days before the date of the price increase was observed, suggesting an anticipation effect. After the onset of the price increase, a cluster of 27 days was detected. When the cigarette price increased due to consumption tax in April 2014, almost no anticipation effect was observed. Conclusions: The population impact of tobacco price increases on smoking cessation may be assessed using Google Trends data. The cluster indicates that a higher cigarette price increase had a higher and longer lasting effect on population interest in cessation, but the impact may continue for a relatively short time. Implications: To examine the duration of the impact of cigarette price increases on population interest in smoking cessation in Japan, Google search data for smoking cessation were analyzed. Between 2004 and 2016, the three highest spikes of monthly RSV were observed in October 2010, when cigarette prices increased by 37%. Analyzing daily RSV data, the detected cluster size around the price increase in 2010 was 52 days, and a cluster period of 25 days before the date of the price increase was observed, suggesting an anticipation effect. The cluster indicates that a higher cigarette price increase had a higher and longer lasting effect, but the population impact continues for a relatively short time. Further increases in the price of cigarettes are necessary.